Evaluation of bioles as biofertilizers in greenhouse potato cultivation - Quispe Garibay, Gian (2025)
Bioles are liquid biofertilizers rich in micronutrients,phytohormones, and beneficial microorganisms thatimprove crop yield, but the specific conditions of thefermentation process are unknown. The objective of thisresearch was to evaluate bioles produced with differentinputs based on a C/N ratio (10, 21, and 30), of organicand inorganic origin, with and without agitation, in termsof their nutritional composition, microbial load, andeffectiveness on potato (Solanum tuberosum L.) cv. Canchan.Twelve treatments were installed, and physicochemical andmicrobiological analyses were performed. In a greenhouse,the bioles were compared with foliar chemical fertilization(20-20-20 NPK) and a control; the fresh weight of foliageand tubers, and the number of tubers, were measured. Theresults indicated that the composition of the bioles depends on the inputs used, and that an acidic pH reduces the presence of coliforms.Bioles 6 and 11 had the highest fresh foliage weight, while the other treatments(bioles 1–5, 7–10, 12, and chemical fertilization) excelled in fresh weight andnumber of tubers. It is concluded that some bioles can match or exceed theeffect of chemical fertilizers, making them a viable and sustainable alternative.